Solid Right Ventricular Compression by Intraventricular Septum-Hematoma Induced after Percutaneous Coronary Intervention. (28th March 2016) - El-Battrawy, Ibrahim; Akin, Ibrahim; Münz, Benedikt; Leistner, David Manuel; Behnes, Michael; Henzler, Thomas; Haubenreisser, Holger; Papavassiliu, Theano; Borggrefe, Martin; Lehmann, Ralf
Abstract : Intraventricular septum-hematoma is a rare complication following percutaneous coronary intervention (PCI). This complication may represent a challenge for accurate diagnosis and treatment. This case report is about a 60-year-old male patient being admitted with an acute coronary syndrome. Despite successful PCI with drug eluting stent implantation into the right coronary artery (RCA) the patient complained about recurrent angina pectoris according to Canadian Cardiovascular Society (CCS) class IV. Cardiac magnetic resonance imaging and transthoracic echocardiography revealed a massive4.9 × 9.2 cm sized end-diastolic septum-hematoma, which compromised right ventricular cavity. Emergent recoronary angiography ruled out further contrast extravasation from the RCA. Conservative treatment was intended after discussion in the "heart-team." The patient completely recovered with nearly complete resolution of the hematoma after 6 months.